2018
DOI: 10.1061/(asce)hy.1943-7900.0001404
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Throttled Surge Tank for Refurbishment by Increase of Installed Capacity at a High-Head Power Plant

Abstract: The Swiss confederation aims to phase out nuclear power production with its Energy Strategy 2050 program by increasing the renewable energy contribution to its overall energy generation. Hydroelectricity, which is the most important form of renewable energy in Switzerland, supplying almost 60% of the electricity in 2015, should increase its production capacity to achieve this goal. The case study presented in this paper focuses on the replacement of the third turbine in the Gondo high-head power plant with a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…A clear definition of the reference velocity v re f was needed [16,17]. For the quantification of head loss at trash racks, the undisturbed cross upstream the structure was used (mean approach velocity) [18].…”
Section: Basic Equationsmentioning
confidence: 99%
“…A clear definition of the reference velocity v re f was needed [16,17]. For the quantification of head loss at trash racks, the undisturbed cross upstream the structure was used (mean approach velocity) [18].…”
Section: Basic Equationsmentioning
confidence: 99%
“…Therefore, the effects of the lower chamber on upsurge and the upper chamber on downsurge are not seen in the sensitivity analysis. The common variable for upsurge and downsurge is D O , and the positive value of sensitivity in Table 3 indicates the lower value of D O is favorable for all the objectives functions, which was also concluded by many researchers [5,6,11]. Damping of surge waves is due to the frictional loss in the headrace tunnel and the surge tank during mass oscillation.…”
Section: Sensitivity Analysismentioning
confidence: 65%
“…Kim et al [4] applied genetic algorithm (GA) and optimized the location and the connector of the surge tank considering safety and cost of the water supply system. Adam et al [5] carried out a 1-D numerical simulation and performed a physical scale modeling test and found that placing a throttle at the bottom of a surge tank is an effective and economical solution to adapt a hydraulic transient. Steyrer [6] compared different types of surge tanks and concluded that the economic surge tank can be achieved with an effective throttling device in connection with surge tanks.…”
Section: Introductionmentioning
confidence: 99%
“…An independent laboratory experiment is advisable based on the importance of such a throttle for the hydraulic system. Those validation experiments and comparisons with measurements at the finished HPP help to further enhance the confidence in the numerical method (Adam et al, 2018a;Gabl et al, 2014a,b). As mentioned by Adam (2017), future research efforts should include a deeper investigation of the transient behavior of such structures.…”
Section: Resultsmentioning
confidence: 95%
“…Stability criteria define the minimum area of the shaft (Thoma, 1910;Ye et al, 1992) and the storage capacity can be enhanced with additional chambers. Large mass oscillations between the surge tank and the upper reservoir can be further damped with the addition of a throttle (Adam et al, 2018a;Li & Brekke, 1989;Vereide et al, 2017). Such a structure can be added in the connection between the surge tank and head race tunnel or at a change of the cross section (Adam et al, 2016a;Richter et al, 2015).…”
Section: Introductionmentioning
confidence: 99%